Influence of banking applications on improving the personal finances of Ajinomoto del Perú Employees - Laguna Lozano, Luis Anthony (2025)
The objective of this research is to analyze the relationship between personal finances and the use of mobile banking applications among Ajinomoto del Perú employees during 2023. To evaluate personal finances, key categories such as consumption, investment, time optimization, and savings were considered, as these influence the adoption of new digital platforms. These categories not only strengthen employees' personal finances, but also contribute to the country's economic growth. The study, which was non-experimental in design and exploratory-descriptive in approach, used a quantitative Likert-type survey (5 levels) applied to a sample of 300 workers in the Lima department, distributed between the administrative headquarters and the manufacturing plant. The survey included 26 questions based on the categories "Banking Applications" and "Personal Finance," validated by five expert judges in the field, with a result greater than 0.60 using Aiken's V calculation. Likewise, the reliability obtained using Cronbach's alpha (0.863) shows a solid level of reliability. The results confirm that frequent use of banking applications is strongly correlated with improvements in employees' personal finances, as it has allowed them to expand their household budget, save, generate new investments, strengthen their economic situation and monthly cash flow, and optimize their time for the benefit of their personal and professional lives. These actions boost the strength of the financial system and, consequently, promote the country's economic development.